2020
DOI: 10.1108/gs-08-2020-0099
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral estimation of soil organic matter content using grey relational local regression model

Abstract: PurposeThis study aims to improve the accuracy of hyperspectral estimation of soil organic matter content.Design/methodology/approachBased on the uncertainty in spectral estimation, 76 soil samples collected in Zhangqiu District, Jinan City, Shandong Province, were studied in this paper. First, the spectral transformation of the spectral data after denoising was carried out by means of 11 transformation methods such as reciprocal and square, and the estimation factor was selected according to the principle of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Its mathematical and physical meaning is clear, and its calculation is simple (Deng, 1985). At present, grey relational degree has been widely used in natural science, social science and engineering management fields (Liu, 2017), such as the analysis of crop yield affecting factors (Chen et al , 2020; Li et al , 2019), flood identification and flood forecast (Feng et al , 2021), evaluation of multilevel dispatching rules in wafer fabrication (Yee et al , 2021), evaluation of technological innovation ability in universities (Sang et al , 2019), hospital readmission prediction based on improved feature selection (Miswan et al , 2021), China's overcapacity industry evaluation with mixed attributes (Hao et al , 2021), decision-making in manufacturing industry upgrading (Yu et al , 2020), hyperspectral estimation of soil organic matter content (Cao et al , 2021) and so on. With the deepening of grey relational analysis, based on the Deng's relational degree model, many scholars put forward B-type relational degree (Wang, 1989), C-type relational degree (Wang et al , 1999), T-type relational degree (Tang, 1995), slope relational degree (Dang, 1994), absolute relational degree and relative relational degree (Liu et al , 2006), similarity relational degree and proximity relational degree (Liu et al , 2011), comprehensive distance relational degree (Cao et al , 2020) and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Its mathematical and physical meaning is clear, and its calculation is simple (Deng, 1985). At present, grey relational degree has been widely used in natural science, social science and engineering management fields (Liu, 2017), such as the analysis of crop yield affecting factors (Chen et al , 2020; Li et al , 2019), flood identification and flood forecast (Feng et al , 2021), evaluation of multilevel dispatching rules in wafer fabrication (Yee et al , 2021), evaluation of technological innovation ability in universities (Sang et al , 2019), hospital readmission prediction based on improved feature selection (Miswan et al , 2021), China's overcapacity industry evaluation with mixed attributes (Hao et al , 2021), decision-making in manufacturing industry upgrading (Yu et al , 2020), hyperspectral estimation of soil organic matter content (Cao et al , 2021) and so on. With the deepening of grey relational analysis, based on the Deng's relational degree model, many scholars put forward B-type relational degree (Wang, 1989), C-type relational degree (Wang et al , 1999), T-type relational degree (Tang, 1995), slope relational degree (Dang, 1994), absolute relational degree and relative relational degree (Liu et al , 2006), similarity relational degree and proximity relational degree (Liu et al , 2011), comprehensive distance relational degree (Cao et al , 2020) and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [20] used PLSR to estimate the SOM contents in forest soil in the Yunnan Province of China and suggested that PSLR after the LFR (logarithmic first-derivative reflectance) transformation was the best method for SOM estimation of forest soil. Cao et al [37] proposed a multiple linear regression (MLR)-based hyperspectral estimation model based on the gray correlation for overcoming the interference of abnormal soil samples on the constructing of linear regression models. Wang et al [38] and Sun et al [39] reported that MLR was the best multivariate technique to predict SOM content of soil.…”
Section: Discussionmentioning
confidence: 99%
“…In order to further improve the estimation accuracy of grey relational identification, Li et al (2016) established a grey relational estimation model with residual error correction and applied it to the spectral estimation of soil water content and organic matter. On this basis, some new estimation models based on grey relational analysis are constantly proposed, such as spectral estimation correction model based on the difference information between the sample to be identified and its corresponding pattern sample (Miao et al, 2018(Miao et al, , 2019, grey relational local regression model (Cao et al, 2020(Cao et al, , 2021, positive and inverse grey relational degree estimation model (Zhong, 2020), estimation model based on greyness of grey number (Ding et al, 2022), grey relational estimation model based on grey information ) and so on. These studies not only enriched the grey system theory and effectively improved the spectral estimation accuracy of soil organic matter content, but also combined statistical analysis and grey relational analysis to effectively deal with randomness and greyness in spectral estimation.…”
Section: Introductionmentioning
confidence: 99%